Development of activity-based mLearning implementation model for undergraduate English Language learning / Muhammad Ridhuan Tony Lim bin Abdullah - Abdullah, Muhammad Ridhuan Tony Lim (2014)
The purpose of the study was to develop an activity-based mLearning implementation model for English Language learning among undergraduates. The development of the model was aimed at how mLearning could be used to support formal learning in aiding students to achieve both learning needs and target course outcomes through networking of language learning activities. Professional Communication Skills course, an undergraduate language course offered in a private tertiary institution was selected as an example to develop the model. The study adopted the Design and Development Research approach, which was introduced by Richey & Klein (2007) to develop the model. Based on the approach, the study was conducted in three phases. Phase 1 involved needs analysis using survey questionnaire that was conducted among 220 undergraduate students to investigate the need to adopt mLearning and consequently the development of the model. Data for this phase was analyzed using descriptive statistics via Statistical Package for the Social Sciences (SPSS) software. Interpretation of the needs analysis was based on the values of mean and standard deviation. Phase 2 adopted the Interpretive Structural Modeling (ISM) method to develop the model via a panel of eight (8) experts. Interpretation of the data was based on the model generated by ISM software and the classification and relationships of elements (learning activities). Phase 3 involved another panel of experts of 48 members to evaluate the model using a modified Fuzzy Delphi technique. The evaluation was based on their responses to a seven-likert linguistic scale survey questionnaire. The ‘threshold’ value (d) was calculated to determine the experts’ consensus for all questionnaire items while the defuzzification (Amax) values for the items would register the agreement (decision) of the experts. The overall findings for Phase 1 indicated that the students owned at least one mobile technology device (98.6%, n = 217) with 82.2% (n = 181) of their devices were at least Level 2.This concluded that the students have the necessary technology access for the incorporation of mLearning in their formal learning. They also showed high acceptance level and intend to use mLearning in their formal English Language course. Thus, the findings necessitated the need for the study to develop the model. Findings from Phase 2 resulted in the development of the model that consisted of 24 formal and informal learning activities determined by a panel of experts. The experts also viewed that the activities could be divided into three learning domains and four activity clusters to facilitate the interpretation of the roles of the activities. Finally, findings from Phase 3 of the study showed consensual agreement (d = 89.9%) among the experts in terms of the selected language activities (Amax = 42.03), relationships among them (Amax = 43.05), the classification of the activities (Amax = 42.05), and the overall evaluation of the model (mean Amax = 41.59) as the values exceeded the minimum value of 33.6. The model proposes how formal and informal learning could converge practically through the incorporation of mLearning activities in formal learning settings in aiding the students to fulfill their language learning needs and target course outcomes.